The investigation of collocation errors in writing of EFL learers’ at Bac Lieu University - Thao, Ngo Ngoc (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2021)
The current study investigates the collocation errors in EFL sophomores’ writing to obtain information about the common collocation errors they use. The design of this corpus is quantitative research which employed document analysis as the instrument to collect data. A total 20 EFL sophomores at Bac Lieu University participated in this study and the samples were obtained through two writings production to check the collocational errors that students made. The data was collected and identified base on the types of collocational errors occurrence in the two writings. The result reveals that students have a tendency of using two common collocation errors the Quantifier + Noun (14.8%), Verb + Preposition (14.8%) more than other types and they are also the top types in which students made errors. Based on the pattern identified, the study suggested some pedagogical implications for lecturers as well as students in using and learning collocations.